Hysteron-proteron: A Polyfunctional Rhetorical Device – with Reference to Arabic-English Translation - Ali, Salah Salim (Meta, 2007)
AbstractHysteron-proteron is one of the rhetorical devices present in all literary works and in almost all literate cultures.Linguistically, it is considered a kind of inversion, topicalization or permutation that occurs on the sentence level and involves deviation in the syntagmatic progression of sentences as well as a semantic shift encompassing scope, focus and emphasis (Jakobson 1972: 78-80) besides fulfilling certain grammatical processes such as interrogation and passivization (Jack et al. 1989).Literarily, hysteron-proteron has a great aesthetic and poetic relevance as it is one of the rhetorical devices that can structurally modify both the texture and sense of the text according to the writer’s taste and intention. In other words, it offers one of the stylistic options that will consequently exercise certain pragmatic impact on the reader.It goes without saying, however, that by virtue of its strong affinity to syntax, semantics and style, hysteron-proteron usually involves translation problems which acquire more salience when the languages hold two diametrically opposing standpoints as is the case with Arabic and English.After expounding hysteron-proteron and, diagrammatically, illustrating its polyfunctionality, an account is provided on its occurrence in prose, poetry and in Arabic sacred literature i.e., the Qur’an, tackling its deeper sedimented layers in the Arab mind. The paper also legislates for the unmistakable impact of Western style of literary expression on some Arabic narrative texts. This just projects one more benefit of translation when used as a probing device in detecting literary borrowing through awkward or blind literal rendering of purposefully-disrupted word-order in English into Arabic or vice versa.